Comparação das características cinemáticas do triplo salto entre atletas de nível nacional e internacional - Fragoso, A. A. M. (School of Education, Communication and Sport, 2019)
The aim of this study was to compare the kinematics of triple jump between athletes from national and international background considering performance data in competition. A sample of 25 athletes (13 from national and 12 from international level) with 24.92±4.48 years was assemble. Two high velocity cameras were used to collect data in a competition context. A single pair of photocells were also used to measure the final velocity of the preparatory running phase. Further analysis included computing the linear and angular kinematic measures from different aspects of the triple jump. Data was retrieved using the Kinovea Software dissecting the athletes` behaviour frame by frame. Considering the linear kinematics, the national level athletes revealed smaller values than their international peers, with 14.71±0.94m in the official jump, 15.01±0.90m in the real jump and 0.30±0.16m for the loss. The international group presented higher values at 16.98±0.45m; 17.05±0.44m and 0.07±0.06m, respectively. The same trend was observed for the partial jumps (hop, step and jump), with the national group presenting lower values (5.27±0.43m; 4.22±0.48m and 5.51±0.42m, respectively) than the international ones (6.02±0.15m; 4.99±0.39m and 6.04±0.31m). The last two steps of the preparation running phase also showed lower values for the national group (2.14±0.15m and 2.04±0.26m for the penult and last steps) comparing with the international cohort (2.35±0.12m and 2.27±0.14m, respectively). The final running mean velocity at the take-off board was again lower for the national athletes (9.16 m/s) compared to the international ones (9.81 m/s). Considering the angular kinematics, little to no differences were observed between the two groups. The trunk angle seemed to be higher in the landing phase than in the jumping phase for all athletes. Moreover, it was also detected that two partial phases (e.g. hop and step) determined most (r = 0.80 and r = 0.62, respectively) the official jump for the national group, while for the international group it was just the step phase (r = 0.89) that presented a higher association with the final result. Our findings suggest that we should expect some differences between kinematics of triple jump when comparing national and international level athletes. Those differences may rely most in the little differences in the angular kinematics which, in consequence, may affect the linear output of the jump. This can be seen in the lower velocity of the final running stages before the jump and the reduced breakdown between the different stages of the overall jump in the national group.